Effects of organic zinc on tibia quality, mineral deposit, and metallothionein expression level of aged hens. (31st August 2018) - Min, Y N; Liu, F X; Qi, X; Ji, S; Cui, L; Wang, Z P; Gao, Y P
ABSTRACT: The study aimed to determine the effects of methionine hydroxy analog chelate zinc on the tibia quality, mineral deposit, apparent retention of nutrients, and liver metallothionein (MT) expression level of aged laying hens. A total of 960 layers (Hy-Line Grey, 57 wk old) were randomly assigned into 4 groups, and each group had 8 replicates of 30 hens. During the first 2 wk, groups were fed a basal diet without extra zinc (Zn: 35.08 mg/kg). During the ensuing 14 wk, 4 levels of Zn (inorganic Zn: 80 mg/kg; organic Zn: 20, 40, 80 mg/kg) were added to the diet. The results indicated that both the Zn source and level did influence tibia strength and calcium (Ca) and Zn concentrations of tibia ( P < 0.05), whereas there were no differences in the copper (Cu) and phosphorus (P) concentrations of the tibia and the tibia length ( P > 0.05). Moreover, dietary supplementation with 40 or 80 mg/kg of organic Zn showed higher Zn and Ca concentrations in the tibia and higher tibia strength. The Cu concentration in the liver showed no difference among the 4 treatments, whereas the Zn concentration in the liver increased with the increasing Zn level. The apparent retention of P, iron (Fe), and manganese (Mn) was not affected by the Zn level or source ( P > 0.05). However, the organic Zn group increased the apparent retention of Cu, Zn, Ca, crude protein (CP), and energy, and the group supplemented with 40 or 80 mg/kg of organic Zn obtained significant effects ( P < 0.05). Moreover, dietary supplementation with 40 or 80 mg/kg organic Zn increased the MT mRNA expression of the liver at week 72, whereas 20 mg/kg of organic Zn decreased it ( P < 0.05). In conclusion, this study suggested that an optimum dietary (40 mg/kg) organic Zn level plays a key role in promoting the apparent retention of minerals and nutrients, trace element deposit, and MT mRNA expression.